Gendered farm work and decision-making: Quantitative evidence from Tajikistan - Mardonova Tolibkhonovna, Mohru; Lambrecht, Isabel B.; Mahrt, Kristi (International Food Policy Research Institute, 2024)
Quantitative data collected in August and September 2018 in 12 districts of Khatlon Province, called “The Assessment of Nutrition-Sensitive Value Chains in the FtF ZOI in Tajikistan” were employed to analyze gender differences in participation in crop production and marketing activities, and to understand the association between women’s employment and their decision-making power at home. The dataset contains general information on the households’ farm activities, and detailed information of production practices for households’ main horticultural crops (vegetables, fruits, melons and cucurbitae).